Behavioral and Psychological Symptoms of Dementia - Cerejeira, Joaquim; Lagarto, Luísa; Mukaetova-Ladinska, Elizabeta (Frontiers in Neurology, 2012)
Behavioral and psychological symptoms of dementia (BPSD), also known as neuropsychiatric symptoms, represent a heterogeneous group of non-cognitive symptoms and behaviors occurring in subjects with dementia. BPSD constitute a major component of the dementia syndrome irrespective of its subtype. They are as clinically relevant as cognitive symptoms as they strongly correlate with the degree of functional and cognitive impairment. BPSD include agitation, aberrant motor behavior, anxiety, elation, irritability, depression, apathy, disinhibition, delusions, hallucinations, and sleep or appetite changes. It is estimated that BPSD affect up to 90% of all dementia subjects over the course of their illness, and is independently associated with poor outcomes, including distress among patients and caregivers, long term hospitalization, misuse of medication and increased health care costs. Although these symptoms can be present individually it is more common that various psychopathological features co-occur simultaneously in the same patient. Thus, categorization of BPSD in clusters taking into account their natural course, prognosis and treatment response may be useful in the clinical practice. The pathogenesis of BPSD has not been clearly delineated but it is probably the result of a complex interplay of psychological, social and biological factors. Recent studies have emphasized the role of neurochemical, neuropathological and genetic factors underlying the clinical manifestations of BPSD. A high degree of clinical expertise is crucial to appropriately recognize and manage the neuropsychiatric symptoms in a patient with dementia. Combination of non-pharmacological and careful use of pharmacological interventions is the recommended therapeutic for managing BPSD. Given the modest efficacy of current strategies, there is an urgent need to identify novel pharmacological targets and develop new non-pharmacological approaches to improve the adverse outcomes associated with BPS.